2019
DOI: 10.1086/701726
|View full text |Cite
|
Sign up to set email alerts
|

Can a Terrestrial Ectoparasite Disperse with Its Marine Host?

Abstract: One of the most extreme examples of parasite adaptation comes from terrestrial ectoparasites exploiting marine hosts. Despite the ubiquity of such ectoparasitism and its ecological and evolutionary importance, investigations of the responses of ectoparasites to conditions encountered on their hosts are rare. In the case of penguins and their ticks, current understanding suggests that ticks freely parasitize their hosts on land but are incapable of surviving extended oceanic journeys. We examined this conjectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 85 publications
(119 reference statements)
1
6
0
Order By: Relevance
“…Our results support our hypotheses that Little Penguin ticks are host-species specific, and that they are capable of considerable aquatic dispersal in association with their hosts. These results are consistent with previous fine-scale genetic studies (McCoy et al, 2012;McCoy, Chapuis, et al, 2005;Moon et al, 2015), and a recent study of Little Penguin tick physiological tolerances (Moon et al, 2019), but are the first to indicate penguin-associated tick movement between landmasses separated by thousands of kilometres of open ocean. Although the ticks showed greater phylogeographical structure than their hosts-which may be due, in part, to the higherresolution markers used in this study, or as a result of the tendency of parasites to show higher levels of genetic structure than hosts (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results support our hypotheses that Little Penguin ticks are host-species specific, and that they are capable of considerable aquatic dispersal in association with their hosts. These results are consistent with previous fine-scale genetic studies (McCoy et al, 2012;McCoy, Chapuis, et al, 2005;Moon et al, 2015), and a recent study of Little Penguin tick physiological tolerances (Moon et al, 2019), but are the first to indicate penguin-associated tick movement between landmasses separated by thousands of kilometres of open ocean. Although the ticks showed greater phylogeographical structure than their hosts-which may be due, in part, to the higherresolution markers used in this study, or as a result of the tendency of parasites to show higher levels of genetic structure than hosts (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Kangaroo and Troubridge Islands in South Australia are only separated by ~60 km of open ocean, and were found to share a single, panmictic tick population. Movement between these colonies is well‐supported by the physiological capabilities of Little Penguin ticks, and, based on average swimming speeds of Little Penguins (1.8 m/sec: Bethge, Nicol, Culik, & Wilson, ), dispersal between them could be achieved by a swimming penguin in under an hour (Moon et al, ). Likewise, population assignments and phylogenetic analyses of the ticks at Oamaru (New Zealand), Wedge Island (Tasmania) and Phillip Island (Victoria) colonies also provide evidence for immigration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dispersal of penguins among colonies, however, necessarily involves aquatic movement, which may restrict tick dispersal (Pugh 1997, Dietrich et al 2011; ticks are generally not found on penguins returning from foraging trips (Pugh 1997). A recent physiological study has found that little penguin ticks I. eudyptidis and I. kohlsi around Australasia can tolerate some conditions faced at sea (e.g., immersion in seawater for a few days and to penguin dive depths; Moon et al 2019a), and phylogeographic work suggests at-sea movement is occurring occasionally at the scale of 10s to 100s of kilometers (Moon et al 2019b). The capacity of the more generalist and widespread Ixodes uriae ticks to disperse with penguin hosts over short or long distances remains, however, largely unknown.…”
Section: Introductionmentioning
confidence: 99%